Aortic Dissection Presenting as Cardiac Tamponade with Hemopericardium Initially Identified by Echocardiography - Khalid Sawalha; Angel López-Candales (Heart Views)
In this case, a 79-year-old white male is seen in the emergency department complaining of acute chest pressure, shortness of breath, diaphoresis, and dizziness that began for 4 h from the time of presentation. Physical examination showed signs concerning for cardiac tamponade in the presence of hypotension. Echocardiography showed a large amount of hemopericardium. We then injected intravenous contrast that became visible within the pericardial space. Chest computed tomography showed Type A aortic dissection. The patient was transferred to a higher-level facility for intervention. We share this rare presentation of spontaneous aortic dissection complicated by cardiac tamponade and hemopericardium.